The Knowledge Level of Medical Students at YARSI University class of 2019 about Hypertension and Its Review by Islamic Perspective - Sahira Nabila Azahra; Rika Ferlianti; Firman Arifandi; Edward Syam (Junior Medical Journal, 2022)
Background: Long-term (persistent) hypertension can harm the kidneys, heart, and brain if it is not caught early and treated effectively.Every year, more people are diagnosed with hypertension, and it is estimated that 9.4 million of these deaths are due to complications from hypertension. In addition to individual negligence, a lack of accurate information about a disease can result in widespread ignorance, which can lead to the rise of health concerns. The key factor contributing to uncontrolled blood pressure, particularly in Asian hypertensive patients, is the lack of understanding about hypertension among healthcare professionals, patients, and the general public.Methods The type of research is descriptive quantitative research with cross sectional. The population of this study were students of the Faculty of Medicine, YARSI University Class of 2019 according to the inclusion and exclusion criteria. A sample of 174 people used consecutive sampling which was conducted on 20 October 2022 – 7 November 2022.Results: In this study, the percentage of respondents with high levels of knowledge was 51.7%, that of participants with sufficient levels of knowledge was 43.7%, and that of participants with poor levels of knowledge was 4.6%.Conclusion: Most of the students who participated in this study's survey had a high level of knowledge about hypertension.